Efecto de la incorporación de Zeolita natural y Mucuna pruriens en el cultivo de arroz (Oryza sativa L.) bajo condiciones controladas en Upala, Alajuela, Costa Rica (Repertorio Científico, 2020)
Two sources of green manure, Mucuna pruriens and Crotalaria spectabilis were used in three different doses: 100, 150 and 250 g/m2. It was possible to determine the dose of 100 g / m2 with M.pruriens as the best in yield, even better than the commercial control and other treatments, also with an acceptable grain quality, also contributing with a better CICE, a lower acidification of the soil and a good incorporation of organic matter to the soil. Other effects and factors involved under the conditions of this trial are discussed
Keywords: Green manure, Mucuna, Zeolita, Rice, Nitrogen